Peer review of the pesticide risk assessment of the active substance Trichoderma atroviride strain AT10. (7th April 2022) - ,; Alvarez, Fernando; Arena, Maria; Auteri, Domenica; Castoldi, Anna Federica; Chiusolo, Arianna; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; Egsmose, Mark; Fait, Gabriella; et al.
Abstract: The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State, France, for the pesticide active substance Trichoderma atroviride strain AT10 and the considerations as regards the inclusion of the substance in Annex IV of Regulation (EC) No 396/2005 are reported. The context of the peer review was that required by Regulation (EC) No 1107/2009 of the European Parliament and of the Council. The conclusions were reached on the basis of the evaluation of the representative use of Trichoderma atroviride strain AT10 as a fungicide on lettuce (field use). The reliable endpoints, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.